2014
DOI: 10.3382/ps.2013-03392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naturally mycotoxin-contaminated corn on nutrient and energy utilization of ducks fed diets with or without Calibrin-A

Abstract: One hundred sixty-two 21-d-old ducks were randomly allotted to 6 treatments with 3 levels of mycotoxin-contaminated corn (0, 50, and 100% M) and 2 levels of Calibrin-A (CA, a clay mycotoxin adsorbent, 0 and 0.1%) to evaluate the effects of increasing levels of mycotoxin-contaminated corn on nutrient utilization in ducks fed diets with or without CA. Endogenous losses were obtained from another 27 ducks. Excreta samples were collected to determine DM, OM, CP, amino acids, and gross energy. Gross energy was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
9
0
3
Order By: Relevance
“…(2013) also reported that AFs caused dramatic reduction in feed intake of meat ducks; reduced feed intake could then lead to decreases in body weight and weight gain. Yang et al. (2014) also found that AF reduced utilization efficiencies of meat ducks with respect to energy and protein feed.…”
Section: Discussionmentioning
confidence: 86%
“…(2013) also reported that AFs caused dramatic reduction in feed intake of meat ducks; reduced feed intake could then lead to decreases in body weight and weight gain. Yang et al. (2014) also found that AF reduced utilization efficiencies of meat ducks with respect to energy and protein feed.…”
Section: Discussionmentioning
confidence: 86%
“…TRAVEL, J.-D. BAILLY, P. GUERRE Les résultats obtenus lorsque différentes mycotoxines sont administrées en mélange avec l'une d'entre elles à des doses toxiques semblent révéler un nombre limité d'interactions. Ainsi, l'administration d'AFB1 à des doses reconnues toxiques associée à des doses non toxiques de fusariotoxines, ne semble pas révéler d'interaction majeure entre ces composés (Lee et al 2012aet b, Wan et al 2013, Siloto et al 2013, Yang et al 2014. Des résultats déjà anciens réalisés avec l'OTA associée à des fusariotoxines vont dans le même sens.…”
Section: / Exposition à Des Contaminations Multiplesunclassified
“…By contrast, combined effects of low levels/doses of toxins are more likely but less well understood [7,8,9,10,11]. Most studies on the combined effects of mycotoxins were done using aflatoxin B1 in association with FUS [12,13,14,15,16,17]. Only very few studies have investigated the combined effects of FUS in poultry.…”
Section: Introductionmentioning
confidence: 99%